Chairside Direct Fabrication of Cheek Plumpers on an Existing Complete Denture for Facial Esthetic Rehabilitation: A Clinical Case Report - Guddolla Venkata Prasanna; Karukayil Amrutha Mohanbabu; Vinnakota Dileep Nag (Journal of Primary Care Dentistry and Oral Health, 2026)
Abstract Esthetic rehabilitation in completely edentulous patients involves restoration of function and facial appearance. Loss of buccal fat, muscular tone, and alveolar bone support may result in sunken cheeks and compromised facial esthetics. Cheek plumpers support the facial musculature but are commonly incorporated during fabrication of new dentures; however, some patients may be unwilling to replace well-fitting existing prostheses. This clinical case report describes the conservative management of a patient unwilling to replace a well-functioning existing maxillary complete denture through direct chairside modification with cheek plumpers using autopolymerizing acrylic resin, thereby providing immediate facial esthetic rehabilitation while avoiding fabrication of a new prosthesis. Polyvinyl siloxane putty impression material was used to achieve adequate cheek support without compromising retention, stability, speech, or mastication. The prosthesis was subsequently converted into a definitive heat-cure hollow prosthesis to improve durability. Follow-up evaluation demonstrated improved esthetics, enhanced retention and stability after rebasing, and patient-reported satisfaction. The described technique provides a simple, economical, minimally invasive, and clinically practical treatment option for patients seeking facial esthetic rehabilitation while retaining a well-functioning existing complete denture.